An industrial report on the Malaysian building information modelling (BIM) taskforce: Issues and recommendations - Ahmad Tarmizi, Haron; Marshall-Ponting, Amanda J.; Zahrizan, Zakaria; Mohd Nasrun, Mohd Nawi; Zuhairi, Abd Hamid; Kamarul Anuar, Mohamad Kamar (Construction Research Institute of Malaysia, 2015)
The government of Malaysia has a vision to become a fully developed country by the year 2020, and the construction industry has a significant role to play in assisting the government to achieve this vision. In order to become an advanced country, the construction players in Malaysia need to be globally competitive, and encouraging innovation in the industry is a key aspect of this is and provides the rationale for the roundtable discussion workshop this paper describes. The main objectives of this roundtable discussion were to establish the Building Information Modelling (BIM) task force, provide a platform for industry experts to discuss BIM issues, share knowledge and information and work collaboratively, and to provide recommendations for policy makers for further enhancements of the construction industry. The exploratory roundtable discussion was used as the research method. This roundtable discussion demonstrated the lack of understanding of BIM by the construction industry in Malaysia and the importance of establishing a BIM task force to promote BIM and National BIM Guidelines in Malaysia. This paper also presents the draft organisational chart for the BIM Taskforce, concludes that Industrial Building System (IBS) should provide one of the directions for this task force to implement BIM and that the next step is to develop a case study to increase knowledge sharing activities amongst practitioners and academics.